HUBUNGAN INTERAKSI DENGAN KOHESI SOSIAL ANGGOTA PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE (PSHT) DI KECAMATAN TAPUNG HULU KABUPATEN KAMPAR - Harfani, Rizki Hizlia; Nurhamlin (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This research was conducted in Tapung Hulu sub-district, Kampar Regency. The aim of this research is to determine the relationship between interaction and social cohesion among members of the Setia Hati Terate Brotherhood in Tapung District, Kampar Regency. This research applies a quantitative approach using validity and correlation tests. The sampling technique in this research was Simple Random Sampling using the Slovin formula which obtained a sample of 124 members. Data collection through questionnaires, observation and documentation. The findings of this research show that there is an interaction relationship with the social cohesion of PSHT members in Tapung Hulu District, where the majority of PSHT members are based on the identity of the first respondent in the 14-40 year age group with 91.9%, male gender 69.4% while female 30.6%, Islamic religion 74.2% while Christianity is 25.8%, black-jambon student belt level is 48%, while trainers are 29.0%, junior high school/vocational school education is 65.3%, and finally unmarried status is 92.7%, while married is 7.3%. The results of the relationship between interaction and social cohesion using SPSS Version 23 obtained a result of 0.000, which means the result is smaller than 0.05. This proves that the higher the social interaction, the higher the social cohesion that PSHT members will have.